2017
DOI: 10.1111/ecoj.12382
|View full text |Cite
|
Sign up to set email alerts
|

Organised Crime, Insider Information and Optimal Leniency

Abstract: When 'low-rank'criminals are o¤ered to cooperate with the justice in exchange of judicial leniency, their information generates ex-post rents that may actually favor their heads and increase the crime pro…tability. Hence, an optimal leniency policy must trade o¤ the positive impact of helpful disclosure of insider information and the positive externality that these rents exert on the organisation's returns from crime.Due to this tension, the amnesty that minimises the probability of crime induces the Legislato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In line with this complicated picture, case law analyses have revealed that the judges more often than not dismiss at least parts of insider witness testimonies (Chlevickaiteė t al., 2021). Regarding reliability concerns, insider witnesses might have unique information that is difficult to corroborate or otherwise authenticate, especially where it comes from a complex or secretive organisation (Aranburu, 2009;Nardini, 2006;Piccolo and Immordino, 2017). This might cause particular issues where such information is highly relevant, as is often the case with linkage evidence (Del Ponte, 2006;Pamsm-Conteh, 2017).…”
Section: Witness Evaluation At the Iccts And The Particular Case Of I...mentioning
confidence: 99%
See 2 more Smart Citations
“…In line with this complicated picture, case law analyses have revealed that the judges more often than not dismiss at least parts of insider witness testimonies (Chlevickaiteė t al., 2021). Regarding reliability concerns, insider witnesses might have unique information that is difficult to corroborate or otherwise authenticate, especially where it comes from a complex or secretive organisation (Aranburu, 2009;Nardini, 2006;Piccolo and Immordino, 2017). This might cause particular issues where such information is highly relevant, as is often the case with linkage evidence (Del Ponte, 2006;Pamsm-Conteh, 2017).…”
Section: Witness Evaluation At the Iccts And The Particular Case Of I...mentioning
confidence: 99%
“…Indeed, at the core of almost every complex criminal case sits and accomplice (or cooperating) witness, a person capable of giving an insider's view of the crimes under investigation… (Cohen, 2002: 817) In evaluating the testimony of Bečir Begovic, the Trial Chamber has balanced his former position as Chief of the Srebrenica Public Security Station and his consequent informed knowledge of the situation, against the interest he may have to disengage the civilian police and himself from the events that took place at the Srebrenica Police Station… 1 Insider or accomplice witnesses are central to complex criminal cases, as demonstrated by the international experiences of investigating and prosecuting members of the mafia, drug cartels or other organised crime groups (Acconcia et al, 2014;Fyfe and Sheptycki, 2014;Nardini, 2006;Piccolo and Immordino, 2017;Wetmore et al, 2020). The principal argument for relying on insiders is the simple lack of reliable alternatives to gain insight into the internal functioning of criminal organisations and the actions of the accused (Combs, 2018;Koumbarakis, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is imposed in most of the existing literature -see, e.g., Piccolo and Immordino (2016). In Section 5.4 we discuss the implications of assuming alternative social goals.…”
Section: =1mentioning
confidence: 99%
“…See, e.g.,Piccolo and Immordino (2016) for a more general analysis of the costs and bene…ts of leniency programs for criminal organizations in the absence of corruption.…”
mentioning
confidence: 99%